Development of Biological Board Game in Immune System to Enhance Critical Thinking Ability for Upper Secondary School Students - Kanna, Peerawit; Chantrsukrit, Pornthep (An Online Journal of Education, 2023)
The objectives of this research were: 1) to investigate the problems and needs associated with using a biology board game on the immune system, 2) to develop a biology board game on the immune system, and 3) to compare the results of using a biology board game on the immune system to promote high school students’ critical thinking abilities. The sample used in this research was divided into two groups: 108 biology teachers and 50 secondary students under the Bangkok Metropolitan Administration’s Office of Basic Education Commission from multi-stage sampling. Data were collected through a questionnaire and a critical thinking ability test, and were analyzed using mean, percentage, standard deviation, and dependent sample t-test. The research findings were as follows: 1) The majority of biology teachers stated that their school has the required facilities and time available and attach great importance to developing students’ decision-making ability. 2) The biology board game on the immune system that was developed was a negotiation and deduction board game. It contains important components, including the player’s role, the game situation, feedback to the player, and a conclusion. 3) The students’ critical thinking ability scores after using the biology board game were significantly higher than before at the .05 level of confidence.